A recepção leitora de Dom Quixote das crianças: da prosa às histórias em quadrinhos - Guollo, Fernanda Maccari (2010)
In order to disseminate the taste for the literary reading it is necessary to find out which genres provide this contact between readers and the literary narratives. This research brings out the analysis of reading reception in Dom Quixote das Crianças, a Monteiro Lobato’s adaptation of Cervantes’ El Ingenioso Hidalgo Don Quijote de La Mancha for children’s literature in the mid-twentieth century and which was also adapted for comics in the 21th century by André Simas. This study presents the historical contextualization of children’s book, the presence of Monteiro Lobato and his adaptations, having Dona Benta as a reading mediator character between the children in the Sítio do Picapau Amarelo (Yellow Woodpecker Farm) and the young readers who are in touch with Lobato’s narrative. ¨There is also an analysis of the book studied and the story adapted for comics, having its historicity mentioned as well. The theoretical background review is based on the Theory of Aesthetics Reception considering its important for the reading reception analysis of a group of students at the age of 12 years old. Then, the study presents the analyses of a Reading Workshop carried out during the research, including a reading circle, narrative illustrations made by students and a questionnaire for further data analysis. Finally, the analysis of students’ answers are presented, they are the reflection of the reading activities. Thus, the present research aims at contributing to young readers’ education, favoring young readers’ encouragement and taste for literary reading with the purpose of promoting and improving children’s cultural and communicative performances as well as suggesting new ways to practice reading inside and outside classrooms. Keywords: Children’s book; Reading Reception; Dom Quixote das Crianças.